THE ABILITY OF STUDENTS TO WRITE DONGENG USING THE TREASURE HUNT GAME METHOD - Evi Hasim; Susilowati (International Journal of Innovations in Engineering Research and Technology, 2020)
The purpose of this study was to describe the students’ ability to write fairy tales using the Treasure Hunt game method in class VI SDN No. 32 Southern Cities Gorontalo City. The type of research that is used is a method of research descriptive. Researchers as instruments as well as data collectors. Activity analysis that is done is examine the data obtained, reducing the data. The results of research on the students’ ability to write fairy tales using the Treasure Hunt game method in class VI SDN No. 32 Kota Selatan Kota Gorontalo out of a total of 2 5 students, there are 20 or 80 % of students capable, 3 or 12 % underprivileged students, and 2 or 8 % of students unable to write fairy tales using the Treasure Hunt game method. It can be concluded that the students of class VI SDN No. 32 Kota Selatan Kota Gorontalo has been able to write tales of the Treasure Hunt game method. As for the suggestion of researchers that should be when teaching must wisely choose the method of learning that correspond to the eye subjects, characteristic of the students, as well as the state of the environment of the school. With this research, hopefully it can be a reference material for further research.